Pelatihan Konten Kreator Berbasis Digital Sebagi Media Penyiaran Ajaran Dharma - Ni Komang Wiasti; I Wayan Wirata; Sri Rahayu Puspawati (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology has created broad opportunities for the dissemination of information, including the dissemination of religious teachings. Digital media not only functions as a communication tool but can also be utilized as an educational medium to spread the values of Dharma to the community. This study aims to describe the implementation of Digital-Based Content Creator Training as a medium for disseminating Dharma teachings using the content management theory approach. This study employs a descriptive qualitative method with data collection techniques including observation, documentation, and literature study. The results show that the digital-based content creator training was carried out through several stages of content management, including content planning, content production, content distribution, and content evaluation. Through this training activity, participants gained an understanding of digital literacy, social media ethics, and skills in producing and distributing creative and educational digital content. The training also had a positive impact on improving participants' abilities to utilize digital media as a medium for disseminating Dharma teachings to the community. Therefore, digital media can serve as an effective medium for spreading the values of Dharma creatively, innovatively, and in accordance with technological developments in the digital era